PERSEPSI WAJIB PAJAK ORANG PRIBADI ATAS PERUBAHAN PTKP DAN TARIF PAJAK SERTA PENGARUHNYA TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Juita Tanjung (Universitas Mercu Buana, 2016)
The change of tax regulations often creates hesitation to people. The low level of awareness to these changes resulting to apathetic attitude that people tend to ignore the obligation as a tax payer. A research would be interesting and useful when identifying about people perception against to the change of tax regulations, in this case is income tax. Perception can be used as a measurement on how people assess the problems or changes. A positive perception to the change of